Landslide susceptibility assessment by implementing the analytical hierarchy process in GIS weight overlay tool: A case study of the Krupanj area in Western Serbia - Đokanović Sonja (Geološki Anali Balkanskoga Poluostrva)
The aim of this paper is to show the susceptibility to sliding in the Krupanj area. Intense rainfall in May 2014 triggered many landslides in western Serbia. The Krupanj area was particularly affected by this event. The material damage occurred affected the awareness of the importance of knowing the locations that are prone to sliding. Therefore, from 2014 to 2021, field research was carried out in the Krupanj area. During this period a large amount of landslide data were collected by engineering geological mapping. These data were used for susceptibility analysis. For present study the analytical hierarchy process (AHP) and weight overlay (WO) tool were used. Nine factors were used for susceptibility analysis: slope, aspect, curvature, elevation, lithology, distance from rivers, faults, boundary’s and land cover. In order to be able to make a comparison, all factors were evaluated using the Saaty scale, so that the weights of the individual factors were obtained. The weight values obtained by AHP were used in GIS tool. Final map was validated by ROC analysis. The validation results show accuracy of 77,1% (good) for model.